Games in Mathematics Teaching: A Practice with Didactic Resources in the Final Years of Elementary School - Paulo Vitor da Silva Santiago; Francisco Cleuton de Araújo; Rosângela da Silva do Amaral de Araújo (Journal of Instructional Mathematics, 2025)
Mathematics learning in Brazilian public schools faces persistent challenges, particularly in relation to students’ mastery of the four basic operations. Traditional methods have often failed to generate interest or engagement, highlighting the need for alternative strategies such as mathematical games. This research analyzes the importance of using games in the mathematics classroom as resources that foster motivation, socialization, and problem-solving. The study adopted a qualitative approach in the form of a case study with sixth-grade students from a public school in Caucaia, Ceará, Brazil. The subjects were selected through convenience sampling, as this group represented students in a critical stage of mathematical development who frequently experience difficulties with arithmetic. Data collection included classroom application of the games Stop Math and Mental Bingo, a student questionnaire, and participant observation. Analysis was conducted through Bardin’s Content Analysis in three stages: game exploration, practical application, and reflection. The results showed that 83% of the students reported feeling motivated by the games, most considered the activities easy to perform, and observations indicated higher levels of concentration, participation, and interaction during lessons. These findings confirm that playful methodologies can strengthen learning of basic operations and make mathematics teaching more engaging, particularly in under-resourced public schools.